In Vitro Study To Evaluate Microleakage After Restoring Pulpotomy Primary Teeth With Several Materials (Journal of Hama University, 2020)
The aim of the study was to evaluate microleakage after restoring pulpotomy primary teeth with several materials (dental amalgam, glass ionomer cement, composite resin, compomer and stainless steel crowns).The sample consisted of 100 primary human teeth (first, second upper and lower molars) with freshly extracted. The pulpotomy was done with formocryzol on the entire teeth of the sample (each sample was formed class II MO or DO).The bottom was filled with zinc oxide and eugenol and then the grade of the zinc phosphate, then distributed evenly and randomly into five groups of 20 groups each: Group 1 has been restored with dental amalgam. Group 2 has been restored with glass ionomer cement. Group 3 has been restored with composite resin. Group 4 has been restored with dental compomer. Group 5 has been restored with stainless steel crowns. After finishing the restorations, all the teeth have been subjected to thermocyclings and have been immersed in 2% Methylene blue solution for 24 hours. The microleakage degree was measured after making buccal-lingual section and was examined by the endoscope.Results: We conclude that the degree of microleakage in GIC and compomer group was higher than that in dental amalgam group, composite resin group, and stainless steel crowns separately. We also conclude that the degree of microleakage of stainless steel crowns was lower than in the dental amalgam group and the composite resin group separately in the research sample.Conclusions: Dental amalgam, composite resin, or stainless steel crowns are preferable for restoring pulpotomy primary teeth rather than glass ionomer cement and compomer. Stainless steel crowns exhibited the lowest values of microleakage  and therefore were considered the best choice in temporary pulp amputations.The leak was only cervical, if any.